Measurement of the Y(1S) pair production cross section and search for resonances decaying to Y(1S)μ+μ− in proton-proton collisions at √s=13TeV; Physics Letters B; Vol. 808 - Sirunyan А. М.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich (2020, 2020)
Title screen